Employing personal reading logs short stories to enhance students’ L2 reading comprehension achievement / Nik Mastura Nik Ismail Azlan ... [et al.] - Nik Ismail Azlan, Nik Mastura; Mohandas, Eliyas Sulaiman; Othman, Salwa; Azhar, Muhammad Aizat (Akademi Pengajian Bahasa, 2019)
This study aims to investigate whether the use of six selected short stories throughout the duration of a 14-week course could enhance students’ reading comprehension achievement at the end of the semester. Out of the six short stories read, three were chosen as in-class assignments known as ‘Personal Reading Logs’ (hereafter, PRLs). One group of semester two Diploma students taking a reading skills course was selected through a convenience sampling method. A pre-test was conducted by having the students answer a past semester reading quiz of which the results would then be compared to their post-test (final reading exam) results. A paired samples t-test revealed no significant difference in the reading scores of the pre-test and the post-test, t (17) = -.265, p > .05. Since the p-value was bigger than 0.05, this indicated that the mean reading score of the post-test (M = 50.556) was not significantly higher than the mean reading score of the pre-test (M = 49.722). Therefore, the null hypothesis which stated that there was no difference in the mean score of the pre-test and post-test was retained. Overall, the result refuted the findings of other studies promoting the effectiveness of using short stories to enhance L2 reading comprehension achievement.